Influencia de bioestimulantes foliares a base de algas marinas, sobre el desarrollo y rendimiento del cultivo de arroz (Oryza sativa L.), bajo riego - Banchon Aguirre, Jair Jazmany (2017)
IX. SUMMARY The present investigation was carried out in the lands of the Experimental Farm "Palmar", belonging to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km. 11,5 of the Babahoyo-Montalvo highway. Its objective was to evaluate the influence of foliar biostimulants based on marine algae on the growth and yield of rice (Oryza sativa L.) under irrigation. The sowing material used was the rice variety SFL-09, three biostimulants based on marine algae were evaluated: Stimplex (Ascophyllum nodosum), Kelpak (Ecklonia maximum), Basfoliar Algae (Durvillea antartica), a chemical control (Cytokin) and an absolute control, applied in different doses and distributed in 8 treatments with 3 repetitions, using the experimental design complete randomized blocks. The mean comparisons were made with the Tukey test at 95% probability. The treatments were applied at 20 and 40 days after the transplant. For the normal development of the crop, all the cultural tasks were carried out, such as weed control, fertilization, irrigation, phytosanitary control and harvesting. The variables evaluated were height from plant to harvest, number of tillers and panicles per square meter, panicle length, number of grains per panicles, weight of a thousand grains, days to flowering, leaf analysis, days to maturation, grain physiology, yield per hectare and economic analysis. The results obtained determined that the applications of biostimulants based on marine algae, influenced the obtaining of adequate levels of nutrients in the plants. No significant statistical differences were found in the agronomic variables number of grains per panicle and days to maturity. The variables tillers per square meter, panicles per square meter, panicle length, number of grains per panicle and weight of one thousand grains, recorded the highest averages with the application of Stimplex in a dose of 1 L / ha. The highest production and the highest net benefit was obtained with the application of Stimplex biostimulant at a dose of 1 L / ha with 7392,28 kg / ha and $ 993,60.